Κοινωνία and μετουσία in Gregory of Nyssa’s Oratio Catechetica Magna - Kapłon, Szymon (Teologia w Polsce, 2023)
This article presents a comparative analysis of the use of the terms κοινωνία and μετουσία in Trinitarian, Christological and soteriological as well as sacramental contexts in Gregory of Nyssa’s Oratio catechetica magna. As a result, we can discover that Gregory consciously and precisely distinguishes between the concepts under discussion and treats the term κοινωνία as a bridge connecting the disputed topics of dogmatic theology. Moreover, the analysis shows that the Bishop of Nyssa’s use of the term κοινωνία betrays his desire to transcend the dialectical understanding of the relationship between unity and difference. Instead of this conception originating in Platonism, Gregory seeks a synthetic account that preserves the autonomy and independence and, simultaneously, the possibility of true unity between God and man. The conclusion of the analysis is the need for further research into the use of the concept of κοινωνία in the works of the youngest of the Cappadocian Fathers.